Concluding Remarks - Vergara-Del Solar, A (Palgrave Macmillan, 2021)
The aim of the book presented here has been to gain a fuller understanding of children’s lives in South America since the 1990s, and how children relate to the institutional world. The task involved establishing connections between neoliberal policies and children s rights, as well as analysing the effects of colonialism and the political transformations affecting the region. In the process, the book has drawn attention to forms of agency and resistance by social movements, political groupings and social actors of various types. While our contributors have referred to specific countries, many of the processes analysed here are present in other areas of the region, whatever the differences between them. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.